2018
DOI: 10.1111/all.13433
|View full text |Cite
|
Sign up to set email alerts
|

Short course of grass allergen peptides immunotherapy over 3 weeks reduces seasonal symptoms in allergic rhinoconjunctivitis with/without asthma: A randomized, multicenter, double‐blind, placebo‐controlled trial

Abstract: BackgroundImmunotherapy with peptide hydrolysates from Lolium perenne (LPP) is an alternative treatment for seasonal allergic rhinitis with or without asthma. The aim of this study was to assess the clinical efficacy and safety of a cumulative dose of 170 μg LPP administered subcutaneously over 3 weeks.MethodsIn a randomized, double‐blind, placebo‐controlled trial, 554 adults with grass pollen rhinoconjunctivitis were randomized (1:2 ratio) to receive 8 subcutaneous injections of placebo or 170 μg LPP administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 29 publications
0
38
0
Order By: Relevance
“…Currently, allergen‐specific immunotherapy (AIT) is the only curative treatment that induces clinical and immunological tolerance to causative allergens in allergic patients . AIT efficiently decreases symptoms of allergic asthma, rhinitis, and insect sting allergy . A primary feature of AIT is to change the course of the disease by changing the underlying pathology on local and systemic immune response .…”
Section: Introductionmentioning
confidence: 99%
“…Currently, allergen‐specific immunotherapy (AIT) is the only curative treatment that induces clinical and immunological tolerance to causative allergens in allergic patients . AIT efficiently decreases symptoms of allergic asthma, rhinitis, and insect sting allergy . A primary feature of AIT is to change the course of the disease by changing the underlying pathology on local and systemic immune response .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies confirmed AIT with grass allergen peptides (170 μg over 3 weeks) 110,111 and depigmented polymerized allergen extracts 112 as safe and effective treatments for local AR caused by grass pollen sensitization. A maximum cumulative dose of 490 μg of the grass pollen peptides was well tolerated with only a few minor adverse reactions.…”
Section: Allerg En Immunother Apy ( Ait )mentioning
confidence: 89%
“…Allergen hydrolysates broaden the number of potential T cell epitopes to optimize T cell and B cell responses while maintaining hypoallergenicity. A phase IIb SCIT study assessed the efficacy and the safety of short‐course AIT with peptide hydrolysates from Lolium perenne (LPP) pollen allergens . The treatment induced a modest reduction in the combined symptom and medication score (18% along the entire pollen season).…”
Section: T Cell Epitope Peptidesmentioning
confidence: 99%